MARKETING COMMUNICATION STRATEGIES OF PT.KONSTRUKSI INTI SEJAHTERA IN SUSTAINING CUSTOMER TRUST IN DELI SERDANG - Amelia Putri Siregar; Muhammad Alfikri Matondang (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines the marketing communication strategies of PT Konstruksi Inti Sejahtera (PT KIS) to maintain customer trust in Deli Serdang Regency. The research was conducted using a qualitative approach combined with a descriptive method. Data was collected through observation, interviews, and documentation related to the company's marketing communication activities. The results show that PT KIS uses a marketing communication approach focused on building customer trust, providing high-quality services, and maintaining long-term relationships with customers. The company introduces its services and builds business relationships through direct communication and various media like its website, Instagram, and YouTube. The company also prioritizes business legality, project portfolio, and commitment to customer satisfaction. PT KIS prioritizes open communication, responsive service, transparency in project execution, and quick and accurate complaint handling to build customer trust. Satisfied customers, no complaints, ongoing partnerships, and more returning customers are proof of the success of this strategy. Therefore, effective marketing communication has shown that building and maintaining customer trust in a construction service company is very important.